Hydrochars, perspective adsorbents of heavy metals: A review of the current state of studies - Marija Koprivica; Časlav Lačnjevac (Zaštita Materijala)
As an alternative to dry pyrolysis, hydrothermal carbonization has been proposed as a promising route for conversion of different wastes into biofuels, adsorbents and specific chemicals. Herein, the application of a wide range of waste biomasses as precursors to obtain hydrochars - efficient adsorbents of heavy metals from wastewaters, using hydrothermal conversion, was reviewed. The efficiency of biosorbents has been discussed with respect to the structural characteristics, reaction parameters, sorption capacities and mechanisms, as well as proposed methods of improving hydrochar's surface reactivity. Altogether, biosorption with hydrochars has been identified as a proper alternative to the existing technologies applied for the removal of toxic metal ions from wastewater streams.